Building Peaceful Coexistence Between Rohingya Refugees And Buffer Com- munities In Langsa City And East Aceh - Wijaya, Yulia Rina (UI Scholars Hub, 2018)
The arrival of Rohingya refugees in East Aceh in 2015 is different, in terms of num- ber and people’s response. From the first week to the beginning of the third month, aids flow in daily, piling up at government warehouses. So many people from the Langsa City and neighbouring areas come to see the refugees or offer helps. Sponta- neous social solidarity is evident out of collective memories of Tsunami disaster and spiritual connection. Impact of Rohingya refugees presence that receive humanitari- an aid from many local, national and international organizations which put refugees too special and full of aid and attentions is creating jealousy from local community who live in poor condition, lack of attention and has minimum access to basic need services. This situation generates conflict resistance, economic transaction, infection disease outbreak and criminal act. The impact of the refugee’s presence is not only limited to legal, political and humanitarian issues, but involving local cultures due to its interaction increasingly open. Refugee Camp location’s proximity to local peo- ple’s residence positions the people as buffer community which should considered as main stakeholder. The interaction between the refugees and the people requires a dialog media, so they are able to understand each other and decline the resistance of social and economic conflicts. The cultural dialogue and campaigns has become a medium that effective to build peace between them.